Source Traffic Modelling for Enhanced UMTS Simulation - Ferreira, Jaime (2005)
Enhanced UMTS traffic generation and activity models are described and characterised, based on population and service penetration values. As a reduced set of scenarios is needed for simulation purposes, scenarios were defined with a selection of the most relevant applications. ON/OFF states have been characterised by appropriate statistical distributions for long-range dependence, and parameters for source traffic modelling have been presented.